2016
DOI: 10.4103/0975-7406.199337
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some novel pyrazolo[3,4-d] pyrimidin-4(5H)-one derivatives as potential antimicrobial agent

Abstract: Objectives:The aim of the present work was to synthesize a novel series of pyrazolo[3,4-d]pyrimidin-4(5H)-one derivatives and evaluate their in vitro antimicrobial activity.Methods:Cyclization of an ortho-amino ester of 1-(2,4-dinitrophenyl)pyrazole with various aliphatic/aromatic nitriles under different reaction conditions such as conventional and microwave assisted synthesis, provided pyrazolo[3,4-d] pyrimidin-4(5H)-one derivatives. All the synthesized compounds were evaluated in vitro for their antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although the table does not display a significant difference in terms of yield, it shows that any type of aggregates formed through supramolecular self-assembly can affect organic catalysis to obtain higher yields in shorter reaction time. In the case of [bmim][OHB] the percent anion-anion aggregates [A 2 + H] À is [25] 2 Cl H H 98 178 (180-182) [26] 3 H H Cl 96 160 (162-164) [26] 4 C 6 H 5 CH=CHCHO 92 150 (151-153) [26] 5 H H OH 82 177 (173-175) [26] 6 H H OCH 3 88 155 (156-157) [26] 7 H OCH 3 OH 96 192 (194-196) [26] 8 H OCH 3 H 96 165 (167-169) [26] 9 H OCH 3 OCH 3 87 165 (167) [27] 10 H H N(CH 3 ) 2 82 192 (191-192) [26] [a] Reaction Conditions: Malononitrile (9 mmol); Benzaldehyde ( [a] CA 2 À is the Base Peak for this case the lowest one but around 80 % [CA 2 ] À depicts that not only the presence of isolated anion but supramolecular aggregation influences organic catalysis. Similar behavior can be observed in three other ILs.…”
Section: Relationship Of Spab and Thermal Stability With Catalytic Ac...mentioning
confidence: 99%
“…Although the table does not display a significant difference in terms of yield, it shows that any type of aggregates formed through supramolecular self-assembly can affect organic catalysis to obtain higher yields in shorter reaction time. In the case of [bmim][OHB] the percent anion-anion aggregates [A 2 + H] À is [25] 2 Cl H H 98 178 (180-182) [26] 3 H H Cl 96 160 (162-164) [26] 4 C 6 H 5 CH=CHCHO 92 150 (151-153) [26] 5 H H OH 82 177 (173-175) [26] 6 H H OCH 3 88 155 (156-157) [26] 7 H OCH 3 OH 96 192 (194-196) [26] 8 H OCH 3 H 96 165 (167-169) [26] 9 H OCH 3 OCH 3 87 165 (167) [27] 10 H H N(CH 3 ) 2 82 192 (191-192) [26] [a] Reaction Conditions: Malononitrile (9 mmol); Benzaldehyde ( [a] CA 2 À is the Base Peak for this case the lowest one but around 80 % [CA 2 ] À depicts that not only the presence of isolated anion but supramolecular aggregation influences organic catalysis. Similar behavior can be observed in three other ILs.…”
Section: Relationship Of Spab and Thermal Stability With Catalytic Ac...mentioning
confidence: 99%
“…Therefore, this combination of EFD and TEL is primarily utilized to treat hypertension as it provides effective control of blood pressure through synergistic mechanism, EFD cause vasodilation of arterioles and TEL counteracts the stimulation of renin angiotensin system (RAS) and is used to reduce the incidence of peripheral oedema [6][7][8]. It was reported that the analytical methods were reported for quantification of efonidipine hydrochloride ethanolate and telmisartan alone and in combination with other drugs but not a single method is reported for the simultaneous estimation of both EFD and TEL [9][10][11][12][13][14][15][16][17][18][19]. Therefore, simple, rapid, accurate and reliable method for simultaneous estimation of these drugs seemed to be necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of heterocycles and their fused derivatives has become a central issue in organic synthesis due to their structural diversity and potential pharmaceutical applications . Fused pyrimidinone ring systems are known to have various chemotherapeutic activities . Isoxazolo[5,4‐ d ]pyrimidinones and pyrazolo[3,4‐ d ]pyrimidinones are potent anticancer agents .…”
Section: Introductionmentioning
confidence: 99%